Geriatric Clinic Business Opportunities in Bandung: Is it Worth Developing? - Akhmad Yogi Pramatirta; Nurdin Nurdin; Rachmat Suyanto; Rabiatul Adwiyah; Tasya Aspiranti; Sri Suwarsi (Penerbit Goodwood, 2025)
Purpose: This study aims to evaluate the feasibility of developing the Bandung Geriatric Centre (BGC) Primary Clinic, which focuses on holistic health services for the elderly, given the increasing elderly population and the complexity of their health needs. Methodology/approach: This study was conducted with a quantitative approach using demographic data, market analysis, location study, technology evaluation, government regulation review, and financial projections. Analyses covered market, operational, human resources, legal, and financial aspects. Results/findings: The results show that the development of BGC is feasible. The market aspect shows good growth potential, the strategic location supports operations, the medical personnel fulfill the service needs, and the legality is in accordance with regulations. From a financial perspective, the project showed a positive value with a Payback Period of 4.03 years, NPV of IDR 428.8 million, and IRR of 15.73%. Conclusion: Bandung Geriatric Centre (BGC) Primary Clinic is considered feasible to develop based on the analysis of market, operational, human resources, legal, and financial aspects, with large market potential, strategic location, availability of sufficient human resources, legal compliance, and profitable financial projections. Limitations: This study remains valid despite the limitations of reliance on secondary data, the scope of competitor analysis being limited to a 2.5 km radius, and financial assumptions that are subject to change due to economic dynamics. Contribution: This study contributes to the development of an integrated holistic approach-based elderly health service model, and is useful for health practitioners, investors in health services, and policy makers.